Assessment of Potential Risks of Dietary RNAi to a Soil Micro-arthropod, Sinella curviseta Brook (Collembola: Entomobryidae) - Pan, Huipeng; Xu, Linghua; Noland, Jeffrey E.; Li, Hu; Siegfried, Blair D.; Zhou, Xuguo (Frontiers in Plant Science, 2016)
RNAi-based genetically engineered (GE) crops for the management of insect pests are likely to be commercialized by the end of this decade. Without a workable framework for conducting the ecological risk assessment (ERA) and a standardized ERA protocol, however, the utility of RNAi transgenic crops in pest management remains uncertain. The overall goal of this study is to assess the risks of RNAi-based GE crops on a non-target soil micro-arthropod, Sinella curviseta, which could be exposed to plant-protected dsRNAs deposited in crop residues. Based on the preliminary research, we hypothesized that insecticidal dsRNAs targeting at the western corn rootworm, Diabrotica virgifera virgifera, a billion-dollar insect pest, has no adverse impacts on S. curviseta, a soil decomposer. Following a tiered approach, we tested this risk hypothesis using a well-designed dietary RNAi toxicity assay. To create the worst-case scenario, the full-length cDNA of v-ATPase subunit A from S. curviseta were cloned and a 400 bp fragment representing the highest sequence similarity between target pest and non-target arthropods was selected as the template to synthesize insecticidal dsRNAs. Specifically, 10-day old S. curviseta larvae were subjected to artificial diets containing v-ATPase A dsRNAs from both D. v. virgifera (dsDVV) and S. curviseta (dsSC), respectively, a dsRNA control, β-glucuronidase, from plant (dsGUS), and a vehicle control, H2O. The endpoint measurements included gene expression profiles, survival, and life history traits, such as developmental time, fecundity, hatching rate, and body length. Although S. curviseta larvae developed significantly faster under the treatments of dsDVV and dsSC than the vehicle control, the combined results from both temporal RNAi effect study and dietary RNAi toxicity assay support the risk hypothesis, suggesting that the impacts of ingested arthropod-active dsRNAs on this representative soil decomposer are negligible.